2019
DOI: 10.1002/jso.25395
|View full text |Cite
|
Sign up to set email alerts
|

Surgeon perception versus reality: Opioid use after breast cancer surgery

Abstract: Background Few guidelines exist for an opioid prescription after breast surgical oncology (BSO) procedures. We sought to characterize opioid prescribing and use patterns by surgery type. Methods Patients (n = 332) undergoing BSO procedure were surveyed one week postoperatively for opioid use. The surgeons were surveyed about pain management preferences surgery type. CPT codes were collected for 2017 to calculate the amount of opioids used by surgery type relative to surgeon preference. Results Mean oral morphi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
11
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(14 citation statements)
references
References 30 publications
1
11
0
2
Order By: Relevance
“…15 The current study adds to our understanding of pain management requirements in this population. There is substantial variation in opioid usage, particularly in breast surgery, 18 where recent work illustrates that opioid prescribing continues to outpace consumption 19 , and guidelines aimed at optimizing multimodal pain regimens are very much needed. 20 Furthermore, our consumption data suggest that prescription sizes may be further reduced without compromising patient satisfaction.…”
Section: Discussionmentioning
confidence: 99%
“…15 The current study adds to our understanding of pain management requirements in this population. There is substantial variation in opioid usage, particularly in breast surgery, 18 where recent work illustrates that opioid prescribing continues to outpace consumption 19 , and guidelines aimed at optimizing multimodal pain regimens are very much needed. 20 Furthermore, our consumption data suggest that prescription sizes may be further reduced without compromising patient satisfaction.…”
Section: Discussionmentioning
confidence: 99%
“…To our knowledge, this is the first prospective randomized controlled study to reveal ropivacaine infiltration of the two drainage exit sites, which significantly reduced postoperative pain and analgesic requirements and improved the quality of recovery after mastectomy. Park's study [10] reported that compared with other breast surgical procedure types, mastectomy required consumption of more opioids during the first week postoperatively. Opioid consumption plays an important role in postoperative pain control after mastectomy.…”
Section: Discussionmentioning
confidence: 99%
“…Park’s study [ 10 ] reported that compared with other breast surgical procedure types, mastectomy required consumption of more opioids during the first week postoperatively. Opioid consumption plays an important role in postoperative pain control after mastectomy.…”
Section: Discussionmentioning
confidence: 99%
“…При нарастании концентрации АФК Nrf2 диссоциирует от Keap1, перемещается в ядро и взаимодействует с антиоксидант-респонзивным элементом (ARE), отвечающим за экспрессию генов, таких как NAD(P)Hхиноноксидоредуктаза 1 (NQO1), гемоксигеназа 1 (HMOX1), глутаматцистеинлигаза (GCL), глутатион-S-трансферазы (GSTs), супероксиддисмутаза 2 (SOD2), глутатионпероксидаза 1 (GPX1), тиоредоксинредуктаза 1 (TRXR1) и каталаза [74][75][76][77], что необходимо для восстановления динамического редокс-гомеостаза в клетке (рис. 4) [11,70,[78][79][80].…”
Section: селенодефицит вызывает воспалениеunclassified